2007
DOI: 10.1371/journal.pone.0000534
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cyr61, CTGF, and WISP-1 Correlates with Clinical Features of Lung Cancer

Abstract: BackgroundCCN family, comprising six members (Cyr61, CTGF, Nov, WISP-1, WISP-2, WISP-3), is involved in the stimulation of cell proliferation, migration, adhesion, angiogenesis, and tumorigenesis. Several studies have shown that expression of Cyr61, CTGF, and WISP-1 affects the tumorigenic potential of lung cancer cells in vitro. However, the correlation of expression of CCN family proteins and clinical features of lung cancer remains unknown.Methodology and Principal FindingsIn the present work, we quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 40 publications
3
124
1
1
Order By: Relevance
“…The first one corresponds to the decreased expression of CCN1 in the tumor site, and the second one refers to the suppression of the tumor inhibitory effects of the residual CCN1 activity through KLK-mediated proteolysis. In addition to CCN1, CCN2 (62) and CCN5 (present study) are down-regulated, whereas CCN4 (62) is up-regulated in NSCLC. These findings indicate that members of the CCN family may play important but contrasting roles in NSCLC progression.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The first one corresponds to the decreased expression of CCN1 in the tumor site, and the second one refers to the suppression of the tumor inhibitory effects of the residual CCN1 activity through KLK-mediated proteolysis. In addition to CCN1, CCN2 (62) and CCN5 (present study) are down-regulated, whereas CCN4 (62) is up-regulated in NSCLC. These findings indicate that members of the CCN family may play important but contrasting roles in NSCLC progression.…”
Section: Discussionmentioning
confidence: 49%
“…In particular in nonsmall cell lung carcinoma (NSCLC), this idea is supported by our findings showing that: (a) KLK12 is coexpressed with several CCNs in the cancerous tissue of patients and (b) full-length CCN1 and KLK12-released CCN1 fragments have different effects on the migration of the A549 lung cancer cell line in vitro. Previous data have indicated that CCN1 may act as a tumor suppressor in NSCLC in vitro and in vivo (61,62). Collectively, these findings suggest that two mechanisms affecting CCN1 could act simultaneously to facilitate NSCLC development.…”
Section: Discussionmentioning
confidence: 59%
“…Potential involvements of WISP-1 in several cancers have been reported (Soon et al, 2003;Chen et al, 2007;Davies et al, 2007), whereas its role in melanoma remains unexplored. We sought to investigate the biological function of WISP-1 in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…For example, WISP1, an effector of activated Wnt signaling previously reported to regulate cell survival, [17][18][19] showed the highest level change (3.6-fold higher in U373-IR than in U373-C). Patient data at the US National Cancer Institute (Repository of Molecular Brain Neoplasia Data (REMBRANDT) 20,21 ) also indicated that upregulation of WISP1 is associated with poorer clinical outcome (Supplementary Figure S2), further substantiating our data.…”
Section: Microarray Analysis Reveals Upregulated Wnt Signaling In U37mentioning
confidence: 96%